2018
DOI: 10.1530/rep-17-0483
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility preservation: past, present and future

Abstract: Anti-cancer therapy, particularly chemotherapy, damages ovarian follicles and promotes ovarian failure. The only pharmacological means for protecting the ovaries from chemotherapy-induced injury is gonadotrophin-releasing hormone agonist, but its efficiency remains controversial; ovarian transposition is used to shield the ovary from radiation when indicated. Until the late 1990s, the only option for fertility preservation and restoration in women with cancer was embryo cryopreservation. The development of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 220 publications
0
77
0
5
Order By: Relevance
“…Currently, in the field of oncofertility, efforts are constantly made to improve existing fertility preservation techniques and to develop new strategies suitable for patients of whatever age and ovarian reserve status (43). Thus, several "fertoprotectant" molecules, such as rapamycin or melatonin, have been developed and studied to limit chemotherapyinduced ovarian damages in mice (18,19,30,44,45). However, these treatments are involved in cell-death mechanism or in ubiquitous signaling pathways, and they could therefore interfere with the efficacy of treatment or other physiologic mechanisms (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in the field of oncofertility, efforts are constantly made to improve existing fertility preservation techniques and to develop new strategies suitable for patients of whatever age and ovarian reserve status (43). Thus, several "fertoprotectant" molecules, such as rapamycin or melatonin, have been developed and studied to limit chemotherapyinduced ovarian damages in mice (18,19,30,44,45). However, these treatments are involved in cell-death mechanism or in ubiquitous signaling pathways, and they could therefore interfere with the efficacy of treatment or other physiologic mechanisms (19).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review focused on the current and future indications and techniques of fertility preservation (17). Preventing chemotherapy-induced ovarian dysfunction might represent an interesting option for preserving optimal chances of natural or medically assisted conceptions after healing (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…To date, various efforts have been made to preserve ovarian function and fertility, for example, administration of gonadotropin‐releasing hormone agonist prior to the initiation of chemotherapy, cryopreservation of embryos, mature oocytes, or ovarian tissue (Pereira et al, ). Although means of ovarian protections (Abir, Fisch, Raz, Nitke, & Ben‐Rafael, ) were attempted to prevent or decrease the loss of fertility before the chemotherapy or radiotherapy (Fisch & Abir, ), current treatments are still highly toxic to gonads such as ovary and testis. When chemotherapy impairs ovarian function, patients present reduced antral follicle counts and low anti‐Müllerian hormone levels that are indicative of a low reproductive potential (Wenners et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another group suggested that the artificial ovary contain isolated follicles in a biomaterial and thus is able to preserve fertility and replace hormonal functions of the ovary with a significantly decreased risk of introducing malignant cells back into patients (Soares et al, ). A recent review described the artificial ovary that contains primordial follicles embedded in a matrix, as one of the promising future FP techniques (Fisch & Abir, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation